Investigation of the antibacterial activity of pioglitazone - Masadeh, Majed M (Dove Medical Press, 2011)
PURPOSE: To evaluate the antibacterial potential of pioglitazone, a member of the thiazolidinediones class of drugs, against Gram-positive (Streptococcus pneumoniae) and Gram-negative (Escherichia coli and Klebsiella pneumoniae) bacteria. METHODS: Susceptibility testing was done using the antibiotic disk diffusion method and the minimal inhibitory concentration (MIC) of pioglitazone was measured according to the broth micro incubation standard method. RESULTS: Pioglitazone induced a dose-dependent antibacterial activity in which the optimal concentration was 80 μM. Furthermore, results indicated that while E. coli was sensitive (MIC = 31.25 ± 3.87 mg/L) to pioglitazone-induced cytotoxicity, S. pneumoniae and K. pneumoniae were resistant (MIC = 62.5 ± 3.77 mg/L and MIC = 62.5 ± 4.14 mg/L, respectively). Moreover, pretreatment of bacteria with a suboptimal concentration of pioglitazone (40 μM) before adding amoxicillin, cephalexin, co-trimoxazole, or ciprofloxacin enhanced the antibacterial activity of all agents except co-trimoxazole. This enhancing effect was particularly seen against K. pneumoniae. CONCLUSION: These results indicate the possibility of a new and potentially important pioglitazone effect and the authors’ ongoing studies aim to illustrate the mechanism(s) by which this antibacterial effect is induced.